Factors associated with polypharmacy in primary care: a cross-sectional analysis of data from The English Longitudinal Study of Ageing (ELSA). Issue 3 (14th March 2018) - Slater, Natasha; White, Simon; Venables, Rebecca; Frisher, Martin
Abstract : Objectives: While older age and ill health are known to be associated with polypharmacy, this paper aims to identify whether wealth, body mass index (BMI), smoking and alcohol consumption are also associated with polypharmacy (5–9 prescribed medications) and hyperpolypharmacy prevalence (≥10 prescribed medications), among older people living in England. Design: Cross-sectional study. Setting: The English Longitudinal Study of Ageing Wave 6 (2012–2013). Participants: 7730 participants aged over 50 years. Data synthesis: Two multivariate models were created. HR with corresponding 95% CI, for polypharmacy and hyperpolypharmacy, were calculated after adjusting for gender, age, wealth, smoking, alcohol consumption, BMI, self-rated health and the presence of a chronic health condition. Results: Lower wealth (lowest wealth quintile vs highest wealth quintile, adjusted HR 1.28; 95% CI 1.04 to 1.69, P=0.02) and obesity (adjusted HR 1.81; 95% CI 1.53 to 2.15, p<0.01) were significantly associated with polypharmacy. Increasing age (50–59 years vs 70–79 years, adjusted HR 3.42; 95% CI 2.81 to 4.77, p<0.01) and the presence of a chronic health condition (adjusted HR 2.94; 95% CI 2.55 to 3.39, p<0.01) were also associated with polypharmacy. No statistically significant association between smoking and polypharmacy (adjusted HR 1.06; 95% CI 0.86 to 1.29, P=0.56) was established; while, very frequent alcohol consumption (consuming alcohol >5 times per week) was inversely associated with polypharmacy (never drank alcohol vs very frequently, adjusted HR 0.64; 95% CI 0.52 to 0.78, p<0.01). The adjusted HR for hyperpolypharmacy was accentuated, compared with polypharmacy. Conclusion: This study has identified that lower wealth, obesity, increasing age and chronic health conditions are significantly associated with polypharmacy and hyperpolypharmacy prevalence. The effect of these factors, on polypharmacy and especially hyperpolypharmacy prevalence, is likely to become more pronounced with the widening gap in UK wealth inequalities, the current obesity epidemic and the growing population of older people. The alcohol findings contribute to the debate on the relationship between alcohol consumption and health.